Dynamic Perfusion CT: Optimizing the Temporal Resolution and Contrast Volume for Calculation of Perfusion CT Parameters in Stroke Patients - Wintermark, Max; Smith, Wade S.; Ko, Nerissa U.; Quist, Marcel; Schnyder, Pierre; Dillon, William P. (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Numerous parameters are involved in dynamic perfusion CT (PCT). We assessed the influence of the temporal sampling rate and the volume of contrast material.METHODS: Sixty patients with ischemic hemispheric stroke lasting ≥12 hours underwent PCT. Groups of 15 patients each received 30, 40, 50, or 60 mL of contrast agent. Regional cerebral blood volume (rCBV), regional cerebral blood flow (rCBF), mean transit time (MTT), and time-to-peak (TTP) maps were calculated for temporal sampling intervals of 0.5, 1, 2, 3, 4, 5, and 6 seconds. Results were statistically compared. Signal-to-noise ratios (SNRs), duration of arterial entrance to venous exit, and radiation dose were also assessed.RESULTS: Increasing temporal sampling intervals lead to significant overestimation of rCBV, rCBF, and TTP and significant underestimation of MTT compared with values for an interval of 1 second. Maximal allowable intervals to avoid these effects were 2, 3, 3, and 4 seconds for 30, 40, 50, and 60-mL boluses, respectively. Venous exit of contrast material occurred in 97.5% of patients after 36, 42, 42, and 48 seconds, respectively, for the four volumes. SNRs did not differ with volume. The effective radiation dose varied between 0.852 and 1.867 mSv, depending on the protocol. The cine mode with two 40-mL boluses and the toggling-table technique with one 60-mL bolus had the lowest doses.CONCLUSION: Temporal sampling intervals greater than 1 second can be used without altering the quantitative accuracy of PCT. Increased sampling intervals reduce the radiation dose and may allow for increased spatial coverage.